2018
DOI: 10.1111/jse.12416
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the flora of Mexico: Dry forests cradles and museums of endemism

Abstract: Mexico is considered an exceptional biogeographic area with a varied endemic flora, however spatial phylogenetic measures of biodiversity have not yet been estimated to understand how its flora assembled to form the current vegetation. Patterns of species richness, endemism, phylogenetic diversity, phylogenetic endemism and centers of neo-and paleo-endemism were determined to examine differences and congruence among these measures, and their implications for conservation. Of 24 360 vascular plant species 10 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
0
22

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 91 publications
(129 reference statements)
10
105
0
22
Order By: Relevance
“…Closely related organisms often share an evolutionarily conservative habitat preference, thus the organisms living together in a particular habitat will tend to be more closely related than expected by chance. Past studies [21,28,29,32] have shown that this was especially prevalent in dry habitats, a pattern which was confirmed here. Significantly low PD was observed in arid areas using both phylogram and chronogram, suggesting another potential explanation for the phylogenetic clustering: recent diversification in situ.…”
Section: Patterns Of Phylodiversitysupporting
confidence: 90%
See 1 more Smart Citation
“…Closely related organisms often share an evolutionarily conservative habitat preference, thus the organisms living together in a particular habitat will tend to be more closely related than expected by chance. Past studies [21,28,29,32] have shown that this was especially prevalent in dry habitats, a pattern which was confirmed here. Significantly low PD was observed in arid areas using both phylogram and chronogram, suggesting another potential explanation for the phylogenetic clustering: recent diversification in situ.…”
Section: Patterns Of Phylodiversitysupporting
confidence: 90%
“…Mishler et al [12] proposed an integrating method called categorical analysis of neo-and paleo-endemism (CANAPE) to quantitatively distinguish between centers dominated by neo-endemism (range-restricted short branches) or paleo-endemism (range-restricted long branches). PE and CANAPE methods add an evolutionary perspective to understanding endemism and have drawn substantial attention [21][22][23][24][25][26][27][28][29][30][31][32][33]. Finding concentrations of endemic taxa and rangerestricted OTUs provides a critical basis for conserving evolutionary history [5].…”
Section: Introductionmentioning
confidence: 99%
“…7A, 7C) indicate a similar rainfall regime in the localities where F. aurea and F. isophlebia occur, while populations from F. cookii and F. tuerckheimii occur in distinct conditions. Ficus cookii is found in a restricted habitat belonging to the Central Depression of Chiapas (Mexico), which is a center of plant diversity and endemism (Sosa et al, 2018). Regarding F. tuerckheimii , this species reaches the highest elevations and values of mean annual precipitation that can be found in the F. aurea complex.…”
Section: Discussionmentioning
confidence: 99%
“…As with Florida, the Neotropical flora at the tip of the Baja California is also likely to have been profoundly shaped through relatively recent dispersal events (Sosa et al, 2018) due to being discontinuous with other Neotropical areas ( Fig. 1) and for its history of inundation by the sea (Durham & Allison, 1960).…”
Section: Tropical Wet and Dry Forestsmentioning
confidence: 99%